Temperature and the Timing of Work - Sam Cosaert; Adrian Nieto Castro; Konstantinos Tatsiramos (Institute of Labor Economics (IZA), 2023)
We leverage U.S. county-day temperature variation combined with daily time use data to examine the effect of temperature on the timing of work. We find that warmer (colder) temperatures increase (decrease) working time during the night and decrease (increase) working time in the morning. These effects are pronounced among workers with increased bargaining power, flexible work schedules, greater exposure to ambient temperature while at work, and fewer family-related constraints. Workers compensate for the shifts in the timing of work triggered by temperature fluctuations by adjusting their sleep time, without changing the timing of leisure and home production activities.
Keywords: J22; Q54; I31; 330; weather; time use; work schedule; labor supply; non-market activities; sleep